Penegakkan Hukum Terhadap Tindak Pidana Penipuan Arisan Online di Indonesia - Saputra EA, Ari Dwi (Universitas Islam Indragiri, 2024)
Information technology basically has benefits for society, but the development of information technology does not escape criminal acts or cybercrime or what is known as cybercrime. In writing this journal, the author uses the library research method by using literature in the form of books, newspapers, records of investigation reports and also previous research. And the formulation of the problem is (1) what is meant by online arisan, (2) criminal sanctions obtained on the perpetrators of online arisan fraud, (3) factors causing online arisan fraud in Indonesia, (4) efforts of the government and society in overcoming the problem of online arisan fraud. And the conclusions are (1) online arisan is an activity carried out by a group of people who have the aim of collecting money regularly in each certain period from each group member through social media, (2) criminal sanctions obtained on the perpetrators of online arisan fraud are listed in the Criminal Code and Law No. 13 of 2008 which has been amended in Law No. 19 of 2016 concerning ITE Law, and this online arisan fraud case is contained in articles 378 to 394 where the perpetrator can be sentenced to a maximum of four years imprisonment, (3) the factors that cause this online arisan fraud in Indonesia are (a) the high unemployment rate and poverty rate, (b) the perpetrator wants to easily get money without working hard, (c) the lack of tools to track the perpetrator, (4) the ease of the perpetrator eliminating traces and (5) the lack of socialization to the community so that people are not aware of the fraud mode itself. (4) the government's efforts to overcome the problem of online arisan fraud (a) conducting socialization to the public about the existence of new crimes regarding online arisan fraud, (b) delivering digital literacy which aims to inform the public so that the public can understand the types of fraud, (c) the government and the Ministry of Communication and Information cooperate in strengthening the regulations of the ITE Law, cyber patrols, digital trust, electronic signature regulations, digital literacy, (d) preparing creative human resources. smart and experts in the field of IT, and (e) preparing creative human resources, The community's efforts in overcoming online arisan fraud are (a) the community is required to have high awareness not to be easily influenced and lulled by the lure given, (b) the community can use services that have been prepared by the government to check the status of account numbers such as the getcontent application, (c) remain vigilant if someone asks for an OTP code either by telephone, sms, email, chat application, (d) be wary of fake sites.